Language as a tool in achieving or failing to achieve the object of desire in Bloodied and Come Back - Shirzad Tayefi; Tohid Shalchian Nazer (مطالعات زبانی و بلاغی)
The concept of desire was particularly important in Freud's teachings, and he paid attention to penis as an important element in male biological structure. Using Saussure's linguistics, Lacan was able to provide a linguistic reading of the concept of desire and penis. Therefore, the Freudian penis gave way to the Lacanian phallus, and desire was also recognized as a linguistic category along with other concepts such as lack and excess. In this research, our qualitative library-based reading of the corpus discusses the position of the phallus as a linguistic factor that always keeps the subject away from objet petit a. The results obtained from the Lacanian reading of the above-mentioned stories show that the characters in these stories have accepted their castration from the very beginning and, with the hope of attaining the phallus, they have entered the field of signification by desiring The big Other, which has in turn referred them from one sign to another. As a subject, these characters have never been able to obtain the object of their desire, and desire as a linguistic matter is always represented by a lack or an excess. The subject's encounter with the lack of the object of desire causes the reproduction of the signifier and preservation of language, and the encounter with the excess of the said object leads to the symbolic death or psychosis of the subject.